CAIXAS ELÉTRICAS DE TOMADAS E FALHAS NA ISOLAÇÃO SONORA DE PAREDES - Bezerra, Angelo de Freitas Duarte; Akutsu, Maria; Brito, Adriana; Aquilino, Marcelo de Mello; Vittorino, Fulvio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The authors verified the effect of the installation of electrical outlets on the reduction of the sound insulation of a masonry wall of cast ceramic blocks, in order to contribute to the improvement of the design of buildings related to this aspect. Tests were carried out to determine the sound insulation index in reverberant chambers and acoustic holography.